Core temperature up to 41.5ºC during the UCI Road Cycling World Championships in the heat. Issue 7 (1st December 2018) - Racinais, Sebastien; Moussay, Sebastien; Nichols, David; Travers, Gavin; Belfekih, Taoufik; Schumacher, Yorck Olaf; Periard, Julien D
Abstract : Objective: To characterise the core temperature response and power output profile of elite male and female cyclists during the 2016 UCI Road World Championships. This may contribute to formulating environmental heat stress policies. Methods: Core temperature was recorded via an ingestible capsule in 10, 15 and 15 cyclists during the team time trial (TTT), individual time trial (ITT) and road race (RR), respectively. Power output and heart rate were extracted from individual cycling computers. Ambient conditions in direct sunlight were hot (37°C±3°C) but dry (25%±16% relative humidity), corresponding to a wet-bulb globe temperature of 27°C±2°C. Results: Core temperature increased during all races (p<0.001), reaching higher peak values in TTT (39.8°C±0.9°C) and ITT (39.8°C±0.4°C), relative to RR (39.2°C±0.4°C, p<0.001). The highest temperature recorded was 41.5°C (TTT). Power output was significantly higher during TTT (4.7±0.3 W/kg) and ITT (4.9±0.5 W/kg) than RR (2.7±0.4 W/kg, p<0.001). Heart rate increased during the TTs (p<0.001) while power output decreased (p<0.001). Conclusion: 85% of the cyclists participating in the study (ie, 34 of 40) reached a core temperature of at least 39°C with 25% (ie, 10 of 40) exceeding 40°C. Higher core temperatures were reached during the time trials than the RR.